2007
DOI: 10.1002/ccd.21016
|View full text |Cite
|
Sign up to set email alerts
|

Impact of renal insufficiency on clinical and angiographic outcomes following percutaneous coronary intervention with sirolimus‐eluting stents

Abstract: Neointimal growth following SES implantation is more pronounced in patients with renal insufficiency, especially those undergoing dialysis, compared with patients with normal renal function. Regardless of the beneficial effect of SES, the increased risk of MACE mainly due to high incidence of target vessel revascularization in the subgroup of patients with renal insufficiency should be taken into account.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
54
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(59 citation statements)
references
References 21 publications
3
54
2
Order By: Relevance
“…Previous studies also demonstrated that major adverse cardiac events and target lesion revascularization rates after SES implantation in HD patients were higher than those of non-HD patients, regardless of the beneficial effect of SESs. 13,14) In the present study, the incidences of any clinical event (50.0%) and target lesion revascularization (33.3%) in the HD group were significantly higher than those of the non-HD group. However, the incidence of target lesion revascularization after BMS implantation in HD patients was 56.3% in the BMS period (from January 2003 to August 2004) at Sapporo Social Insurance General Hospital.…”
Section: Discussionmentioning
confidence: 40%
“…Previous studies also demonstrated that major adverse cardiac events and target lesion revascularization rates after SES implantation in HD patients were higher than those of non-HD patients, regardless of the beneficial effect of SESs. 13,14) In the present study, the incidences of any clinical event (50.0%) and target lesion revascularization (33.3%) in the HD group were significantly higher than those of the non-HD group. However, the incidence of target lesion revascularization after BMS implantation in HD patients was 56.3% in the BMS period (from January 2003 to August 2004) at Sapporo Social Insurance General Hospital.…”
Section: Discussionmentioning
confidence: 40%
“…The higher prevalence of high platelet reactivity in the CKD population might be another potential explanation for the higher incidence of nonfatal target vessel MI in the CR group than in the IR group among CKD patients. This finding suggests that excessive PCI with DES implantation might be associated with procedure‐related or stent‐related long‐term adverse outcomes rather than the benefit of revascularization as previous studies have suggested 1, 33, 34…”
Section: Discussionmentioning
confidence: 69%
“…Although interventional strategies have been tried to overcome atherosclerosis in patients on HD, beneficial effects are limited. For example, patients with end-stage renal failure on hemodialysis and treated with drug-eluting stents for coronary artery disease are at high risk of restenosis after PCI (18,19), although drugeluting stents significantly reduce the risk of restenosis after PCI in many patients (20 -24). Under such conditions, significant improvement in long-term clinical outcome was observed with cilostazol in the study presented here.…”
Section: Discussionmentioning
confidence: 99%